Characterization Of The Time-Averaged Overall Heat Transfer In A Direct-Injection Hydrogen-Fueled Engine - M. M., Rahman; Khalaf, I. Hamada; A. Rashid, A. Aziz (Elsevier, 2012)

(untitled)
This paper presents a description of the time-averaged heat transfer in a direct-injection hydrogen-fueled engine. A computer simulation of the overall heat transfer process within the in-cylinder was run. The experimental results were used to validate the adopted numerical model. One-dimensional gas dynamics were used to describe the flow and heat transfer in the components of the engine model. The engine model was simulated while varying the engine speed, equivalence ratio (φ), and start of injection (SOI) timing, respectively, as follows: 1800 ≤ rpm ≤ 5000, 0.2 ≤ φ ≤ 1.2, and 130° ≤ SOI ≤ 70° before top dead center. The baseline model of the hydrogen-fueled engine was verified through the experimental results, and reasonable agreement was achieved. The results show that the equivalence ratio has a significant impact on the time-averaged heat transfer characteristics. This is a unique behavior that appears in the case of hydrogen-fueled engines due to the wide flammability range. Delaying the injection timing caused different behavior of the time-averaged characteristics of heat transfer. This is an indication of remarkably poor combustion because there is insufficient time for fuel injection before the initiation of the combustion process.